2022
DOI: 10.1007/s12144-022-03339-w
|View full text |Cite
|
Sign up to set email alerts
|

How does psychological capital lead to better well-being for students? The roles of family support and problem-focused coping

Abstract: Recent studies have shifted the attention on the beneficial role of psychological capital from workplace to academic contexts. Moreover, the mediating role of psychological capital in the effect of social support on student outcomes remains unknown. This topic has become more imperative under the pandemic. The current study aimed to investigate the impact of psychological capital on students’ well-being with family support as an antecedent and problem-focused coping as a mediator. Two hundred and eighty-one st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 82 publications
3
18
0
Order By: Relevance
“…Similarly, this study found that the six-factor model fitted the data better than did the five-factor model for both the CSS-36 and the CSS-18. These findings resonate with the stress and coping model (42,43). In particular, the COVID-19 pandemic is a stressor that may affect people's reactions and behavior in various ways (9,30).…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, this study found that the six-factor model fitted the data better than did the five-factor model for both the CSS-36 and the CSS-18. These findings resonate with the stress and coping model (42,43). In particular, the COVID-19 pandemic is a stressor that may affect people's reactions and behavior in various ways (9,30).…”
Section: Discussionsupporting
confidence: 66%
“…Hence, the prediction and finding that AIM high school profiles would relate to IMW over a two-decade period is of importance inasmuch as early development of AIM has significant outcomes for the individuals’ work lives as they advance in adulthood and their careers. The contexts of high school, and work in adulthood, provide appropriate settings for development of intrinsic motivation with similarities in the motivational contexts for school and workWang, et al, (2022) stated that school and organizational settings are similar in behavioral expectations, task nature, and predicted outcomes. As intrinsic motivation is applicable to children and adults, AIM provides a foundation for intrinsic motivation in work.…”
Section: Discussionmentioning
confidence: 99%
“…They planned their valuable time with their family members. During an adverse time like a lockdown and pandemic, social support from family and peers increases individuals' psychological well-being (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%